Effects of spraying surfactants in a fluidised bed on the rehydration behaviour of milk protein isolate powder. (February 2020) - Wu, Shaozong; Fitzpatrick, John; Cronin, Kevin; Maidannyk, Valentyn; Miao, Song
Abstract: Milk protein isolate (MPI) powder is a difficult to rehydrate powder displaying poor wettability and slow dissolution. In this study, MPI powder was top-sprayed with surfactants (Tween 80 and lecithin) in a fluidised bed to investigate the effect of surfactants on the rehydration behaviour. The wetting behaviour of MPI covered by the surfactants was greatly improved except for 4% lecithin. The wetting time of lecithinated MPI decreased to 42 s compared with MPI of 36 min. The Tween coated powders and larger size fractions displayed faster wetting attaining a minimum wetting time of 15 s. The rate of dissolution was not influenced by the presence of the surfactants as the particles continued to slowly dissolve. Broadband acoustic resonance dissolution spectroscopy (BARDS) showed that the gas release behaviour of surfactant covered MPI was totally altered and accelerated in comparison to the MPI powder, especially for Tween 80. Highlights: Both Tween 80 and lecithin coating improved wettability of MPI powder. Tween 80 coating displayed best improvement in wettability. Tween 80 and lecithin did not improve the dissolution of MPI powder. BARDS showed much faster release of gas from surfactant-coated powders.